Scientific publications at a Turkish medical school - (:unkn) unknown (HANLEY & BELFUS INC, 2000)
The authors studied the scientific publishing trend for 1991 to 1998 at Turkey's Marmara University School of Medicine. Although publications increased both in real numbers and in ratios per faculty member, most were not original, peer-reviewed articles. Mere quantity of publications cannot accurately reflect a school's research reputation.